2015
DOI: 10.1007/s11947-015-1471-6
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of Shigella flexneri in Ground Beef and Vibrio cholerae in Seafood with Bacteriophage-Assisted High Hydrostatic Pressure (HHP) Treatment

Abstract: Virulent bacteriophages (VP) and high hydrostatic pressure (HHP) were studied for the inactivation of Shigella flexneri in ground beef and Vibrio cholerae in salmon and mussels. Inoculated foods were treated individually with HHP (150-450 MPa for 5 and 9 min, 300 MPa for 13 min, and 550 MPa for 5 min), with phages (cocktail of 3S. flexneri or single V. cholerae phages, both applied at 10 9 PFU/mL) or combinations thereof (HHP/VP, VP/HHP). Stand-alone treatments with VP, HHP below 450 MPa (seafood) or 550 MPa (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Depending on the type of food product, up to~600 MPa pressure is applied [9]. It has also been shown that combinations of HPP and biocontrol agents, such as virulent bacteriophages and bacteriocins, have synergistic effects in the inactivation of the target pathogens in food [34,35]. The pressure tolerance level varies between different species, strains, and even isolates [16,19,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the type of food product, up to~600 MPa pressure is applied [9]. It has also been shown that combinations of HPP and biocontrol agents, such as virulent bacteriophages and bacteriocins, have synergistic effects in the inactivation of the target pathogens in food [34,35]. The pressure tolerance level varies between different species, strains, and even isolates [16,19,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Some examples are the application of various temperature treatments [39,40], X-ray irradiation [41], Îł-irradiation [42,43], ozone [44][45][46][47], and the application of high hydrostatic pressure (HHP) alone [48] or combined with bacteriophages [48]. The effectiveness of the use of the combination between several of the previous techniques, such as the high hydrostatic pressures combined with a moderate heating [49], or the high hydrostatic pressures combined with the use of bactericidal phages [48], was also demonstrated (Table 3). However, the bivalves die during these processing techniques, modifying their nutritional and organoleptic characteristics; because of this, the application of these techniques is only useful on products that are going to be commercialized or transformed and never on fresh products [36].…”
Section: Depuration By Physical Methodsmentioning
confidence: 99%
“…In the last decade, several alternative processing and preservation technologies have been developed to enhance the safety of food. For example, bacteriophages have been investigated as antimicrobial agents in food systems, including meats, cut fruits, vegetables and milk ( Leverentz et al, 2001 ; Whichard et al, 2003 ; Tabla et al, 2012 ; Chibeu et al, 2013 ; Ahmadi et al, 2015 ; Murray et al, 2015 ; Radford et al, 2017 ). Bacteriophage preparation such as LISTEX TM P100 and LMP-102 are approved by regulatory agencies as processing aids, for use in raw and RTE foods to combat L. monocytogenes contamination ( U.S. Food and Drug Administration, 2006 ; Health Canada, 2011 ).…”
Section: Introductionmentioning
confidence: 99%